Pesona keindahan Alam Taman Nasional Gunung Rinjani Lombok - Tania Maya Puspita (Universitas Palangka Raya, 2023)
Mount Rinjani has a crater about 10 km wide and there is a crater lake called Lake Segara Anak with a depth of about 230 m. The charm possessed by Mount Rinjani is perfect, so there is no doubt that Rinjani is an attraction that can attract the interest of foreign and domestic tourists to climb it. And climbing Mount Rinjani will certainly become memories and life experiences that will not be forgotten. The qualitative research method is a research method that produces descriptive data. The researcher aims to describe the phenomenon that occurs regarding Mount Rinjani Tourism Development in Lombok and its Impact on Tourist Interests. The natural phenomenon of Mount Rinjani which later became a tourist attraction was framed in the Rp. 10 denomination. 10.000 issued by Bank Indonesia in 1998. For climbers, Lake Segara Anak is a favorite location to unwind after steep valleys, savanna, entering the wilderness. Mount Rinjani National Park is the second highest volcano in Indonesia, not only that, Guning Rinjani National Park also has very beautiful natural beauty and there is a wealth of flora and fauna which is the intersection of the wallace boundary, namely the flora and fauna typical of Asia and Australia meet. By introducing the flora and fauna that exist on Mount Rinjani, starting from those that are often encountered. The conclusion of this article is that Mount Rinjani National Park is the second highest volcano in Indonesia, not only that Guning Rinjani National Park also has very beautiful natural beauty and there is a wealth of flora and fauna which is the intersection of Wallace's boundary lines, namely flora and fauna typical of Asia and Australia meet.